Hope Intervention Against Depression in the Survivors of Cold Lava Flood from Merapi Mount. (6th January 2015) - Retnowati, S.; Ramadiyanti, D.W.; Suciati, A.A.; Sokang, Y.A.; Viola, H.
Abstract: The series of Mount Merapi eruptions, which involved a big explosion on 26 October 2010, had been made the damages. It caused the residents, especially those having responsible for other people such as mothers, volunteers, teachers and village apparatus, get depressed. They went through so much depression because besides as survivors their beings were important to others. Therefore, the impacts they felt were not only physical but also psychological. In addition to depression, they were attacked by anxiety. The subjects of this research were groups of mothers, volunteers, teachers and village officials of Sirahan Village, Magelang Regency. Intervention of Hope to lessen depression was taken to them in order to help them face the post-disaster situations. Hope Intervention covered session aiming to identify goals, plan strategies and strengthen motivation to reach the goals. The intervention was taken in four-time meeting with duration of more or less two hours per meeting. The research used a design involving untreated control group with dependent pre-test and post-test and waiting list control group. The control group was given the same treatment after the research process ended. The scores gained by both groups were analyzed with Mann-Whitney Test. The data resulted from observation were analyzed qualitatively. Both analyzing methods showed that there was significant difference of the average of depression rate between the experiment group and the control group at the pre-test and post-test with the value of F = 11.589; p=0.001 (p<0.05). This result showed that hope intervention had significant influence on decreasing the depression rate in the experiment group compared with that in the control group. Therefore it can be concluded that Hope Intervention can lessen depression in the survivors of natural disaster.